2015
DOI: 10.1016/j.bspc.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Yawn analysis with mouth occlusion detection

Abstract: One of the most common signs of tiredness or fatigue is yawning. Naturally, identification of fatigued individuals would be helped if yawning is detected. Existing techniques for yawn detection are centred on measuring the mouth opening. This approach, however, may fail if the mouth is occluded by the hand, as it is frequently the case. The work presented in this paper focuses on a technique to detect yawning whilst also allowing for cases of occlusion. For measuring the mouth opening, a new technique which ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The same approach was also utilized in [29] by using the CNN model on EEG signals. The authors reported that deep-learning methods achieved better accuracy compare to traditional machinelearning algorithms [21][22][23][24].…”
Section: Related Workmentioning
confidence: 99%
“…The same approach was also utilized in [29] by using the CNN model on EEG signals. The authors reported that deep-learning methods achieved better accuracy compare to traditional machinelearning algorithms [21][22][23][24].…”
Section: Related Workmentioning
confidence: 99%
“…The computer vision method mainly uses image processing technology to detect the driver's behavior characteristics to judge the driver's drowsiness. These behavioral features mainly include head movement, blink frequency, eyelid closure, yawning, facial expressions, and the like [9,16]. The performance of this method is greatly affected by the ambient light intensity and other factors.…”
Section: Related Workmentioning
confidence: 99%
“…Azim et al [12] presented a system in which the yawning detection method used Viola-Jones face detection to locate the face, extracted the mouth window, and then searched for the lips through spatial fuzzy c-means clustering. Ibrahim et al [13] proposed a method to detect yawning based on mouth opening, mouth covering and facial feature distortions. Then classification of local binary patterns (LBP) features extracted from the mouth when covered by a hand is used for mouth-covered detection.…”
Section: Related Workmentioning
confidence: 99%